Rare earth element characterization of Bledug Kuwu Mud Volcano, Central Java, Indonesia, based on geochemical analyzes (Susceptibility, XRF, XRD, SEM-EDS and ICP-EOS) - Indriana, Rina Dwi; Saputra, Hijrah; Mariyanto, Mariyanto; Agustin, Eleonora; Iryanti, Mimin; Hapsoro, Cahyo Aji (Penerbit Universiti Kebangsaan Malaysia, 2023)
Mud volcano material is generally rich in oxides, while oxides are the main compounds forming rare earth elements. Bledug Kuwu, Central Java, Indonesia, is one of the active mud volcanoes, so there may be rare earth elements. This research is the characterization of rare earth elements (REE) in the Bledug Kuwu mud using magnetic and geochemical methods. Magnetic characterization uses magnetic susceptibility measurements. The geochemical characterization of the mud samples consisted of the XRF (X-Ray Fluorescence), XRD (X-Ray Diffraction), ICP-EOS (inductively coupled plasma) test, and the SEM-EDS (Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy) test. The results of the geochemical analysis of the Bledug Kuwu mud sample were the content of quartz, kaolinite, and calcite with an average concentration of 42.26%, 23.67%, and 33.96%. The susceptibility of Kuwu’s mud is 0 because the concentration of metal elements is low; according to the results of XRF, XRD, and SEM tests identified the main mud elements as C, O, Si, Ca, and Al. The rare earth elements in Kuwu’s mud are Ce, Dy, Eu, Gd, Ho, La, Nd, Pr, Sm, Tb, Y, and Sc. The highest concentrations were Ce 52.22 ppm and La 47.95 ppm.